Family knowledge on child care with acute lymphocytic leukemia in protective isolation - Ellen Pessoa Rocha; Arinete Veras Fontes Esteves; Elizabeth Texeira; Marcos Vinícius Costa Fernandes (Universidade Federal de Santa Maria, 2017)
Aim: to describe family members' knowledge about child care with acute lymphocytic leukemia in protective isolation. Method: this was a qualitative and descriptive study, carried out in the isolation of the Reference center for oncohematological diseases of the Northern Region, inManaus, through a semi-structured interview with 11 relatives, from January to March 2016. Data were analyzed through Thematic Analysis. Results: from the categories: "Protective Isolation as infection prevention: is it still a seven-headed animal?" and "Protective Isolation Care: everyone needs information" it was possible to observe that the isolation has several facets. For instance, protection, prevention and the separation experienced by the family in this environment (whose routine is differentiated in order to care for the leukemic child). Conclusion: family members know little about child care in isolation and are permeated with doubts and anxiety. They have been willing to learn and suggest the construction of an educational material to facilitate the empowerment of content